Retinoic acid receptor responder protein 2 and intelectin-1 in visceral adipose tissue from pregnant women with gestational diabetes mellitus - Betsy Corina Sosa García; Araceli Consuelo Hinojosa Juárez; María del Carmen García García; Carlos Jhovani Pérez-Amado; Silvia Jiménez-Morales; Hugo Mendieta Zerón (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2023)
Introduction: The adipose tissue secretes chemerin and omentin related to metabolic diseases. It has been reported that both proteins encoded by retinoic acid receptor responder protein 2 (RARRES2) and intelectin-1 (ITLN1) genes, respectively, are abnormally expressed in gestational diabetes mellitus (GDM). Aim: To evaluate the expression of these genes in visceral adipose tissue in pregnant women with GDM. Methods: Descriptive cross-sectional study, with two groups, (A) GDM and (B) control group (pregnant women without GDM). Body mass index (BMI), blood pressure, lipids, and glucose were measured. RARRES2 and ITLN1 mRNA expression were evaluated using quantitative real-time Reverse transcription-polymerase chain reaction using TaqMan probes. Statistical analysis was performed using Kolmogórov–Smirnov, Pearson-Spearman correlation, Kruskal–Wallis tests, and R language with Shapiro–Wilk, SPSS V21.0. Results: Sixty-six women were included. Women with normal weight were more frequent in the control group (33.3%) than GDM (15.2%); overweight was similar in both groups (45.5%), and obesity was less common in the control group (21.2%) than GDM (39.3%). No differential expression of RARRES2 and ITLN1 genes among cases and controls were found, but RARRES2 expression differed (P = 0.016) between normal-weight and overweight women in the control group, and ITLN1 expression significantly differed (P = 0.002) between overweight and obese women in the GDM group. Conclusions: ITLN1 could have a role in the GDM severity based on the BMI of the patients.